The use of social networks as a source of information at civic risk - Cancelo Sanmartín, Mercedes (2015)
Institutions committed to public safety are among its obligations to keep the public informed about various events related to the safety hazards in the environment. When the link between institutions and society is fragmented, citizens seek alternative sources of information as they are online social networks that currently seems to be reliable because the legitimacy of their public, making information and opinion leaders. However, this investigation should be considered that the perception of individuals based on the information that flows through traditional social networks and online turn can createphenomena of misinformation and victimization.